2005
DOI: 10.1007/s00415-005-0595-4
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation lowers brain glutamate levels in Huntington?s disease

Abstract: There is evidence from in vitro and animal experiments that oral creatine (Cr) supplementation might prevent or slow down neurodegeneration in Huntington's disease (HD). However, this neuroprotective effect could not be replicated in clinical trials, possibly owing to treatment periods being too short to impact on clinical endpoints. We used proton magnetic resonance spectroscopy ((1)H-MRS) as a surrogate marker to evaluate the effect of Cr supplementation on brain metabolite levels in HD.Twenty patients (age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 55 publications
1
63
0
6
Order By: Relevance
“…Bender et al, 90 Verbessem et al, 142 Matthews et al, 150 Tabrizi et al, 146 Kasparova et al 39 Evaluation of striatal allografts in primate model of HD Palfi et al 114 Evaluation of ciliary neurotrophic factor in primate model of HD Mittoux et al 115 Metabolic profiling of blood sera from HD patients Underwood et al 122 Alzheimer's disease Metabolic characterization to improve the understanding and diagnosis of AD Fernandez et al, 40 Pfefferbaum et al, 41 Cheng et al, 48 Frederick et al 127 Schizophrenia Metabolic characterization of human brain tissues from schizophrenic patients Prabakaran et al 17 Bipolar disorder Biomarker evaluation Gallelli et al 33 …”
Section: Preclinical Metabonomic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bender et al, 90 Verbessem et al, 142 Matthews et al, 150 Tabrizi et al, 146 Kasparova et al 39 Evaluation of striatal allografts in primate model of HD Palfi et al 114 Evaluation of ciliary neurotrophic factor in primate model of HD Mittoux et al 115 Metabolic profiling of blood sera from HD patients Underwood et al 122 Alzheimer's disease Metabolic characterization to improve the understanding and diagnosis of AD Fernandez et al, 40 Pfefferbaum et al, 41 Cheng et al, 48 Frederick et al 127 Schizophrenia Metabolic characterization of human brain tissues from schizophrenic patients Prabakaran et al 17 Bipolar disorder Biomarker evaluation Gallelli et al 33 …”
Section: Preclinical Metabonomic Studiesmentioning
confidence: 99%
“…90,[142][143][144][145][146] Creatine has several potential neuroprotective effects, including buffering intracellular mitochondrial energy reserves, stabilizing intracellular calcium, and inhibiting activation of the mitochondrial permeability transition pore, which have all been linked to apoptotic and oxidative cell death. Initial pilot 1 H MRS studies have shown alterations in glutamate and glutamine ratios after creatine treatment that may be indicative of creatine enhancing the energy-dependent conversion of glutamate to glutamine, which has been shown to be perturbed in HD.…”
Section: The Use Of Metabonomics In Development Of Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Creatine also improved brain bioenergetics in a dose-ranging 31 P MRS study of adolescent females with drug-resistant depression (Kondo et al 2016). Yet, several clinical studies reported low-to-medium therapeutic potential of creatine to positively dysfunctional energy metabolism in Huntington's disease (Bender et al 2005) and Parkinson's disease (Bender et al 2006), also schizophrenia (Kaptsan et al 2007). Co-administration of creatine and ketogenic diet did not result in 31 P-MRS visible changes in muscle energy metabolism in patients with McArdle disease although the intervention showed some energy-independent beneficial effects (Vorgerd and Zange 2007).…”
Section: Tackling Impaired Bioenergeticsmentioning
confidence: 99%
“…Third, the administration of creatine could result in a decreased release of glutamate. This may be achieved either through increased glutamate uptake into synaptic vesicles, which is an energy-dependent process, ( Xu et al, 1996) or by an increased conversion of glutamate to glutamine (Bender et al, 2005). Finally, creatine supplementation may inhibit the opening of the PTP through the action of Mi-Ck (Beal, 2003;Kroemer et al, 2007).…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%